Spanish validation of NODS screening in a Chilean representative sample - Oyanedel, Juan Carlos (2025)
In a probabilistic and representative sample from Santiago, Chile, this research aims to validate the Spanish-language National Opinion Research Center DSM-IV Screen for Gambling Problems (NODS) and its abbreviated form for the Chilean context. 1032 individuals were surveyed at home using a standardized questionnaire. Results show high reliability for both lifetime and past-year versions of the screening, with structural validity supported by factor analyses. The study found 2.4% of the sample classified as lifetime pathological gamblers and 0.8% for the past year, consistent with higher ranges of international studies. Severe gambling disorder rates are higher in Chile compared to Spain. Concurrent validity suggests that the lengthy Chilean adaptation of NODS is reliable for assessing gambling problems.Keywords: gambling; gambling problems; validation.